ELEMENTOS GENÔMICOS REPETITIVOS NO COMPLEXO Astyanax scabripinnis (TELEOSTEI, CHARACIDAE) - Barbosa, Patrícia (2013)
The most part of the eukaryote genomes is constituted for repetitive DNA or multiple copies DNA, which has already been considered as “junk”, may be associated to the heterochromatin. In this study three Astyanax scabripinnis populations from Pindamonhangaba and Guaratinguetá (SP, Brazil) rivers and stream and one population from Maringá (PR, Brazil) were analyzed about the nucleolar organizing region (NORs), As51 satellite DNA, 18S and 5S rDNA location. Moreover, repetitive sequences were isolated and mapped through Cot-1 technique, which showed homology with UnaL2, a LINE type retrotransposon. The fluorescent in situ hybridization (FISH), with the isolated built retrotransposon probe, evidenced disperse labeled and stronger in centromeric and telomeric chromosomes regions, co-located and interspersed with the 18S DNAr and As51, proven by the fiber-FISH technique. The B chromosome of those populations showed very conspicuous labeled with the LINE probe, also co-located with the As51 sequences. The NORs were actives in a single site of a homologue pair in all three populations, with no evidence that the transposable elements and repetitive DNA have influence in its regulation at the performed analyzes level.